Graph biological relevance - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the exponential relationship between the percentage of links in a given network and the percentage of observed inter-patch movements of caribou and moose that occurred between connected nodes for that individual, in a given year (2005-2009) (Figure 3).